2021
DOI: 10.1136/ejhpharm-2021-002933
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medium-term adverse reactions induced by the first and second dose of mRNA BNT162b2 (Comirnaty, Pfizer-BioNTech) vaccine: a post-marketing Italian study conducted between 1 January and 28 February 2021

Abstract: Objectives On 21 December 2020 the European Commission granted conditional marketing authorisation in the European Union for the anti-COVID-19 mRNA vaccine Bnt162b2 (Comirnaty, Pfizer/BioNTech). The main endpoint of this epidemiological, observational, prospective and monocentric study was to identify the number, types, and severity of adverse events following immunisation that occurred in subjects who had been previously infected with COVID-19, and in those who had not, after vaccination with Comirnaty, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 19 publications
22
39
3
Order By: Relevance
“…Published literature showed that side effects were more prevalent in females than in males and in people aged 55 years or younger than in those older than 55 years [22][23][24]. Similarly, our data also showed that in children between 12-18 years, female participants reported more side effects than males.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Published literature showed that side effects were more prevalent in females than in males and in people aged 55 years or younger than in those older than 55 years [22][23][24]. Similarly, our data also showed that in children between 12-18 years, female participants reported more side effects than males.…”
Section: Discussionsupporting
confidence: 85%
“…Pain/redness at the injection site (90%), fatigue (67%), fever (48%), and headache (55%) were the most frequently reported side effects by the study participants (Figure 1). The data from the present study are in support of the data from clinical trials as well as other real-world studies [20][21][22][23][24]. For example, in phase 3 clinical trials of the BNT162b2 vaccine, the three most common events after the first dose were injection-site pain (71-83%), fatigue (34-47%), and headache (25-42%) [21].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, this condition was not included in the final multivariate model and should be further investigated comparing convalescent COVID-19 cases and controls. In a study [ 37 ], a significant increase of adverse events after vaccination was observed amongst individuals who had previously been infected compared with those who had not, and the number of previously infected subjects who experienced side-effects after the second dose was lower compared with those who were not previously infected. Similar conclusions were observed elsewhere [ 38 ] because infected subjects had higher risk of moderate systemic symptoms after the first dose as compared to individuals naive to the virus and showed a lower risk after the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…The usual post-vaccination observation time that lasts 15-30 minutes does not fully capture the AEs that may appear 1-2 weeks after vaccination (108). Both patients and clinicians should carefully monitor AEs since those who had previously been COVID-19 infected might experience AEs after first doses, and who had not been infected could get AEs after the second dose (124).…”
Section: Risk-benefit Assessment and Should Mg Patients Be Vaccinated?mentioning
confidence: 99%